LEARNING MEANINGFUL VOCABULARY OF ENGLISH FOR STUDENTS AT LEVEL A2 - Luqmonovna, Odinayeva Nilufar; Shamsiddinovna, Valiyeva Nilufar (International Journal of Psychosocial Rehabilitation, 2020)
English level A2 - the second level of language proficiency in the CEFR Pan-European System, a system for determining various language levels compiled by the Council of Europe. In everyday speech, this level can be called basic. The term elementary is the official level description in CEFR - this is the main level. A student who has mastered the basic level of English can satisfy his basic communication needs.